2018
DOI: 10.3171/2017.8.peds17357
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sagittal alignment in patients with adolescent idiopathic scoliosis: is it corrected by surgery?

Abstract: OBJECTIVECervical sagittal alignment (CSA) is related to function and quality of life, but it has not been frequently studied in patients with adolescent idiopathic scoliosis. This study aimed to reveal the change in CSA following corrective surgery, compare the cervical sagittal parameters according to curve types, and assess related factors for postoperative aggravation of CSA.METHODSThe authors studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…In doing so, we demonstrated that these deformities are relatively common and that they are not associated with changes in lumbar lordosis (Table 6 and Figure 4). Similar changes in sagittal alignment have been described cephalad [33][34][35][36][37][38][39] and/or caudal [40][41][42] to posterior instrumentation in children with adolescent idiopathic scoliosis. However, we are not aware of any other reports describing these changes we have observed in the SMA population.…”
Section: Discussionsupporting
confidence: 69%
“…In doing so, we demonstrated that these deformities are relatively common and that they are not associated with changes in lumbar lordosis (Table 6 and Figure 4). Similar changes in sagittal alignment have been described cephalad [33][34][35][36][37][38][39] and/or caudal [40][41][42] to posterior instrumentation in children with adolescent idiopathic scoliosis. However, we are not aware of any other reports describing these changes we have observed in the SMA population.…”
Section: Discussionsupporting
confidence: 69%
“…More recently, restoring sagittal alignment has also received increasing attention in AIS patients, correlating with positive health-related quality of life (HRQOL) outcomes in multiple studies (3,4). Additionally, it has been suggested that a dynamic inter-play may exist between the degree of thoracic kyphosis and nearby cervical and lumbar curvatures (1,2,(5)(6)(7)(8)(9)(10)(11). Multiple studies have emphasized the importance of restoring thoracic kyphosis in the hypo-kyphotic AIS patients to maintain a normal lumbar lordosis (3,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In this realm, cervical sagittal alignment (CSA) has also emerged as one of the variables that may correlate with clinical and functional outcomes in AIS patients undergoing surgical correction (5,6,8,10,11). Previous studies have noted a prevalence of cervical kyphosis in the AIS population, and that thoracolumbar fusion results in alternations in cervical sagittal profile (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Straightened or kyphotic cervical alignment is well recognized in cases with AIS, [6][7][8][9] and not only the thoracolumbar spine but also the cervical spine is affected in AIS. Although scoliosis progressed even after adulthood in AIS, 15,16 the current study found that the sagittal alignment also altered, and the risk of cervical SCC increased.…”
Section: Discussionmentioning
confidence: 99%